Analgesia, anaesthesia and obstetric outcome in women with inherited bleeding disorders. (August 2019) - Boyd, Sean C.; O'Connor, Anna D.; Horan, Maebh A.; Dicker, Pat; Manning, Catherine; Lynch, C.; Regan, C.; Ryan, K.; Tan, T.; Byrne, B.M.
Abstract: Objective: Vertebral canal haematoma (VCH) complicates 1 in 168, 000 obstetric epidurals (Ruppen et al., 2006). This risk is increased in women with inherited bleeding disorders (IBD). The impact of a contraindication to regional anaesthesia on pain management and obstetric outcome in these women is unknown. The purpose of this study was to determine anaesthetic use and obstetric outcomes in a cohort of women with IBD. Study design: 97 women with IBD that delivered 130 babies at the CWIUH from Jan 2011 to Dec 2016 were identified from a maternal medicine database. Multidisciplinary planning of peripartum care was communicated to labour ward staff using a simple checklist. The primary bleeding disorders were: Von Willebrands disease (VWD) Type 1 27 (27.8%); VWD Type 2A 3 (3.8%); Low VWF 3 (3.8%); Bleeding disorder of unknown aetiology (BDUA) 19 (19.6%); deficiency of Factors VII, VIII, IX, X, and XI 13 (13.4%); Carriers of Factor VIII, IX, X, XIII deficiency 17 (17.5%); 5 had combined deficiencies (5.2%) and there was one platelet function defect. 9 had a family history of a bleeding disorder (9.3%). Haemostatic support, analgesia, mode of delivery and maternal and fetal outcomes were compared between pregnancies where regional anaesthesia was permitted and those that were not using the Chi-squared test. Results: When pregnancies where regional anaesthesia was not recommended (49) were compared with pregnancies where regional anaesthesia was considered safe (81), the women were more likely to see an anaesthetist before labour 46 (94%) vs 46 (61%): p < 0.001; to require prophylactic haemostatic support for delivery 30 (61%) vs 1 (1%): p < 0.001; to use a remifentanil infusion 15 (31%) vs 0: p < 0.001, and have general anaesthesia for Caesarean Section (CS) 10 (20%) vs 1(1%): p < 0.001. Vaginal birth 35 (71%) vs 53(65%): p = 0.4 and CS rates 14 (29%) vs 26 (32%) p = 0.28 were similar. Postpartum haemorrhage (PPH) was more common 11 (24%) vs 9(12%) vs p = 0.07 but not statistically so. There were no cases of neonatal bleeding or VCH. Conclusion: Contraindication to neuraxial blockade in labouring women with IBD does not influence mode of delivery. This information is reassuring to these women who may be anxious about delivery without regional anaesthesia.